Deep-sea freezer - Kawagucci, Shinsuke; Matsui, Yohei; Nomaki, Hidetaka; Chen, Chong (Frontiers in Marine Science, 2023)
Recovery of samples from the deep ocean in pristine condition is difficult due to large environmental differences between the deep and surface waters through which the samples necessarily must be transported. Here, we propose a concept for deep-sea sample recovery: a deep-sea freezer using thermoelectric cooling capable of generating ice in the deep and recover them frozen on-board ships. As a proof of concept, we present the DSF-α, a prototype Deep-Sea Freezer based on Peltier device rated at 2000 m. In situ assessments of the DSF-α on remotely operated vehicles showed its capacity to reach freezing (-13.0°C) temperatures in the deep, as well as recovering seawater frozen on deck. Although the DSF-α is limited in that achieving sufficient freezing for useful sample recovery is time consuming, the deep-sea freezer opens a whole frontier of new possibilities for preserving various types of deep-sea samples and has the potential to be adapted according to various needs of the deep-sea research community. With the first literal ‘marine snow’ in the deep, we offer a glimpse to a future where the recovery of reliable bathyal samples is no longer laborious.